Fostering Students’ Grammatical Competence Through Flipped Classroom - Firdausa Fadhilah; Ratna Sari Dewi; Zaharil Anasy; Ismalianing Eviyuliwati; Syauki Syauki (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThis study aims to identify whether Flipped Classroom strategy can enhance students’ grammatical competence. EFL students still found difficulties in understanding and mastering grammar despite its central role in learning a new language. As we are living in the digital era, we can optimize digital tools in teaching and learning to assist students and teachers. Furthermore, students nowadays are tech-savvy, so it would not be very difficult to integrate technology into classroom. The participants of this research were the tenth grade students at SMAN 4 Tangerang Selatan. Classroom Action Research (CAR) was implemented as the research design with two cycles which comprised three meetings in each cycle. The cycle consisted of planning, acting, observing, and reflecting. The instruments used were test, questionnaire, observation, and researcher’s field note. The results showed that 77.14% of students passed the minimum criterion score; further, the results among pre-test, post-test 1, and post-test 2 significantly increased. These findings indicate that Flipped Classroom have the potential to improve students’ grammatical competence. ABSTRAKStudi ini bertujuan untuk meningkatkan kompetensi gramatikal siswa melalui strategi Flipped Classroom dan untuk mengetahui bagaimana strategi tersebut meningkatkan kompetensi gramatikal siswa. Siswa yang menggunakan bahasa Inggris sebagai bahasa asing (EFL) masih mengalami kesulitan untuk memahami dan menguasai tata bahasa meskipun peran sentralnya dalam belajar bahasa. Karena kita hidup di era digital, kita dapat mengoptimalkan alat digital dalam proses belajar-mengajar untuk membantu siswa dan guru. Selain itu, siswa saat ini sudah paham teknologi sehingga tidak terlalu sulit untuk mengintegrasikan teknologi ke dalam kelas. Melihat fenomena ini, oleh sebab itu, penelitian telah dilaksanakan. Subjek penelitian ini adalah siswa kelas X di SMAN 4 Tangerang Selatan. Penelitian Tindakan Kelas (PTK) dilaksanakan sebagai desain penelitian dengan dua siklus yang terdiri dari 3 pertemuan di setiap siklusnya. Instrumen yang digunakan adalah tes, angket, observasi, dan catatan lapangan peneliti. Hasil penelitian menunjukkan bahwa 77,14% siswa dinyatakan lulus kriteria ketuntasan minimal (KKM). Hasil pre-test, post-test 1, dan post-test 2 meningkat secara signifikan yang menunjukkan bahwa Flipped Classroom dapat meningkatkan kompetensi gramatikal siswa.